Understanding community assembly rules in managed floodplain food webs. Issue 2 (2nd February 2021) - Corline, Nicholas J.; Peek, Ryan A.; Montgomery, Jacob; Katz, Jacob V. E.; Jeffres, Carson A.
Abstract: Community assembly has been an important topic in ecological research and theory for over a century. Recently, restoration ecologists have emphasized the use of community assembly rules, such as environmental filtering, to better inform management actions. Although there has been a strong call for the use of community assembly rules in terrestrial restoration ecology, few studies have examined their potential use in providing habitat benefits such as food resources to native species in large‐scale managed aquatic ecosystems. In this study, we found evidence of deterministic community assembly mechanisms in zooplankton communities in floodplain and seasonally inundated off‐channel habitats in California's Central Valley. Additionally, we found that all sampled off‐channel floodplain habitat types had similar zooplankton communities and that assembly in floodplain habitats was governed by variables associated with increased water residence time. This study is the first to determine community assembly rules in floodplain‐river ecosystems in order to assist managers in providing floodplain food‐web benefits to native fish and wildlife species at the landscape scale.